Heritage tourism in peripheral areas : development strategies and constraints - Fonseca, Fernando Pereira da (2012)
Heritage tourism has been widely seen in the last years as an effective way of addressing the socio-economic problems and the heritage degradation of peripheral territo- ries. Heritage is a rising tourism product providing tourists with experiences based on the (in)tangible remains of the past. Due to the lack of other possibilities, the policies found in peripheral territories often highlight tourism – particularly heritage tourism – as the most valuable activity to launch a more sustainable development process. Nevertheless, the impact of heritage tourism is controversial and not always evident both in terms of socio-economic regeneration and in terms of heritage rehabilitation, contradicting some generalized rhetoric. The article presents the main conclusions of research undertaken in the Portuguese peripheral municipality of Almeida, where heritage tourism is claimed to be the most promising activity to overcome the current trend of decline.Data were collected frommunicipal and regional entities using a previously structured survey about perceptions and attitudes towards heritage tourism development in the municipality. The ﬁndings disclose the main obstacles, the strategies and the challenges that this territory is facing to underpin development based on heritage tourism. The main conclusions highlight the strong fragmentation between public and private entities and the lack of a tourism management plan for Almeida’s successful future as a destination of heritage tourism. In certain ways, and due to similar problems, the ﬁndings and the proposals of the present research can be applied to other peripheral areas.